Peran Sikap Keuangan Syariah dalam Memediasi Pengaruh Pengalaman Keuangan dan Social Influences terhadap Persepsi Inklusi Keuangan Mikro Syariah - Umuri, Khairil; Nurlina, Eka; Muftahuddin, Muftahuddin (Jurnal Samudra Ekonomi dan Bisnis, 2026)
Despite Aceh’s strong sharia financial regulations, a gap persists between regulatory strength and public adoption of sharia microfinance institutions. This study examines the effects of financial experience and social influences on sharia microfinance inclusion, with attitude towards sharia finance as a mediating variable among the Acehnese population. Data were collected from 400 respondents using purposive sampling and analyzed through SEM-PLS. The results indicate that financial experience does not have a significant direct effect on sharia microfinance inclusion, whereas social influences exert a significant positive effect on sharia microfinance inclusion. Attitude towards sharia finance shows a strong effect on inclusion and mediates the effects of financial experience and social influences on sharia microfinance inclusion. These findings highlight attitudes towards sharia finance as a key mechanism in bridging the regulatory-adoption gap and advancing sharia microfinance inclusion in Aceh.